Recurrence of surgically treated parasagittal meningiomas: a meta-analysis of risk factors - Balik, Vladimir; Kourilova, Pavla; Sulla, Igor; Vrbkova, Jana; Srovnal, Josef; Hajduch, Marian; Takizawa, Katsumi (Acta neurochirurgica, 2020)
BACKGROUND: As the predictive role of many risk factors for parasagittal meningioma (PM) recurrence remains unclear, the objective of the meta-analysis was to make a comprehensive assessment of the predictive value of selected risk factors in these lesions. METHODS: Studies including data on selected risk factors, such as histology, tumor and sinus resection, sinus invasion, tumor localization, and immediate postoperative radiotherapy for PMs recurrence, were searched in the NCBI/NLM PubMed/MEDLINE, EBM Reviews/Cochrane Central, ProQuest, and Scopus databases, and analyzed using random effects modeling. RESULTS: Thirteen observational studies involving 1243 patients met the criteria for inclusion in the meta-analysis. WHO grading of meningiomas was identified as the most powerful risk factor for recurrence. WHO grade II meningiomas (OR 11.61; 95% CI 4.43-30.43; P < .01; I2 = 31%) or composite group of WHO grades II and III (OR 14.84; 95% CI 5.10-43.19; P < .01; I2 = 48%) had a significantly higher risk of recurrence than benign lesions. Moreover, an advanced sinus involvement (types IV-VI according to the Sindou classification) (OR 3.49; 95% CI 1.30-9.33; P = .01; I2 = 0%) and partial tumor resection (Simpson grades III-V) (OR 2.73; 95% CI 1.41-5.30; P = .03; I2 = 52%) were associated with a significantly higher risk of recurrence than their counterparts. CONCLUSION: Among the selected risk factors, high-grade WHO lesions, advanced sinus invasion, and partial tumor resection were associated with a higher risk of PM recurrence, with WHO grading system being the most powerful risk factor.
Keywords: Meningeal Neoplasms; Humans; lidé středního věku; Neurosurgical Procedures; Meningioma; Female; rizikové faktory; Aged; dospělí; Meta-analysis; senioři; lidé; Parasagittal meningioma; Adult; Postoperative Complications; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Risk factors; Recurrence; meningeom; lokální recidiva nádoru; mužské pohlaví; meningeální nádory; Neoplasm Recurrence, Local; neurochirurgické výkony; Risk Factors